Assessment for Learning in EBE/CLIL : a learning-oriented approach to assessing English language skills and curriculum content at early primary level - Xavier, Ana Cristina da Costa Mano (2016)
Assessment is usually viewed as an inevitable event in teachers' and learners’ lives resulting from an imposition from education systems. However, if done well, assessment can provide learners, teachers and other stakeholders with sound information about learner performance and progress which will ultimately boost learning and feed into school success. This project work discusses ways of assessing both English language and curriculum content at early primary level and aims to provide learning-oriented guidelines and a principled framework for such assessment. It is meant for learners and teachers involved in Early Bilingual Education/Content and Language Integrated Learning at early primary level.